Legal Protection For Pharmacists And Consumers In Online Drug Purchase Transactions Through Market Places - I Gusti Ngurah Uttarayana Angligan (jurnal.unprimdn.ac.id, 2025)
The development of digital technology is driving changes in drug distribution patterns through online transactions in marketplaces, which poses challenges in legal protection for pharmacists and consumers. This study aims to examine the forms of legal protection that apply and the effectiveness of existing regulations. Using a normative juridical method with a statutory and conceptual approach, elaborating on primary, secondary, and tertiary legal materials, this study found that although several regulations exist, their implementation has not been optimal in addressing the complexities of online drug transactions. Regulatory updates that are adaptive to technology, strengthened oversight, and consumer and pharmacist protection are needed to create a safe and accountable drug distribution system.